Women as leaders in education : succeeding despite inequity, discrimination, and other challenges - Martin, Jennifer L. (Women and careers in management., 2011)
This up-to-date, candid examination of women's careers in education and leadership in education describes the pitfalls, triumphs, and future promise of female leaders in education.